2018
DOI: 10.1186/s12891-018-2230-4
|View full text |Cite
|
Sign up to set email alerts
|

Individuals with mild-to-moderate hip osteoarthritis have lower limb muscle strength and volume deficits

Abstract: BackgroundIndividuals with advanced hip osteoarthritis (OA) exhibit generalized muscle weakness of the affected limb and so clinical practice guidelines recommend strength training for the management of hip OA. However, the extent and pattern of muscle weakness, including any between-limb asymmetries, in early stages of the disease are unclear. This study compared hip and knee muscle strength and volumes between individuals with mild-to-moderate symptomatic and radiographic hip OA and a healthy control group.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 45 publications
11
65
0
1
Order By: Relevance
“…However, there were consistent data for lower hip abductor strength in people with hip OA compared with healthy controls (9,10,(22)(23)(24)30). Adding to the literature, our study found beneficial associations of larger CSA of hip adductors with better function and quality of life in hip OA.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, there were consistent data for lower hip abductor strength in people with hip OA compared with healthy controls (9,10,(22)(23)(24)30). Adding to the literature, our study found beneficial associations of larger CSA of hip adductors with better function and quality of life in hip OA.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies reported lower volume and CSA of hip adductor muscles and decreased hip adductor strength in people with hip OA compared with healthy controls (10,22) Other studies investigating pain and injury reported a lower hip adduction/abduction strength ratio in soccer players with groin pain compared with those without groin pain (15) and that hip adductor strength was decreased both preceding and during the onset of groin pain in football players (16). Although these studies investigated adductor strength rather than CSA, the findings indicate the importance of hip adductor muscles when considering pain and recovery for better function.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Cases References to GMedS Loureiro A et al 129) Patients with symptomatic hip OA (n=19) Hip abd. strength was significantly decreased compared with controls GMed volume was not significantly decreased compared with controls Zacharias A et al 130) Patients with unilateral Hip OA (n=20)…”
Section: Reportmentioning
confidence: 99%
“…Die Beobachtung zeigt sich kon sistent in weiteren Studien. Aktuell ist eine verminderte Muskel dichte und -Atrophie auch bei Patienten mit milder Coxarthrose gezeigt worden [35]. Aus diesen Beobachtungen ergibt sich, dass die muskuläre Beeinträchtigung am Beginn der Erkrankung steht und nicht die Folge der etablierten Arthrose ist.…”
Section: Muskulaturunclassified